PENGARUH PEMBERIAN AIR REBUSAN BUAH PAPAYA DALAM MENINGKATKAN PRODUKSI ASI IBU NIFAS DI PUSKESMAS MANUTAPEN - aning pattypeilohy (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
Infant and under-five mortality rates are a measure or parameter of a country's welfare. At least there are 3 causes that contribute 75% of the causes of AKB itself, one of which is diarrhea, the incidence of diarrhea in infants can be caused by errors in giving the right food to the baby, where babies have been given food other than breast milk before entering the age of 6 months. But in Indonesia only 49% of babies breastfeed exclusively for up to 6 months. Consuming papaya boiled water is one way to increase milk production. The purpose of this study was to determine the effect of giving papaya fruit stew to increase breast milk production in postpartum mothers at Manutapen Health Center in 2018. The research design used was Pre Experimental with the design of the One Group Pretest Posttest. The number of samples in this study were 16 people, with a purposive sampling method. Measurements were made before and after being given papaya stew water for 7 days with an observation sheet. The results of the Wilcoxon test showed that most or 87.5% of mothers experienced increased milk productivity. with a value of ρ value of 0.001 <α (0.05), this indicates that there is a significant effect of ASI production before and after being given papaya fruit boiled water. Keywords: Breast milk, Production, Papaya